Enzymatic Spectrum of Herbal Plants Plumbago Linn. - Poul, B.N.; Mukadam, D.S.; Jadhav, B.V.; Dama, L.B. (Asian Journal of Chemistry, 2010)
The family Plumbaginaceae have been surveyed for enzymatic screening in roots of the plants Plumbago Linn. In the present enzymatic screening all the four species of Plumbago were used viz., Plumbago indica, or Plumbago rosea, Plumbago zeylanica, Plumbago capensis and Plumbago albus or Plumbago europea etc. The root extracts of the selected plants are used in ayurvedic digestive formulations, have shown effect of gastro-intestinal flora normaliser. The investigations were directed into the possibilities of the presence of some powerful enzyems, viz., hydrolases, invertase, proteases, oxido-reductases, glucoxidase in the root power of Plumbago species. The statistical data show the presence of the above enzymes in the ratio maximum 10.35 and minium 1.35 units per dry weight in Plumbago zeylanica, Plumbago capensis, Plumbago rosea and Plumbago albus respectively. The Plumbago zeylanica Linn. bearing white flowers shows greater effect on digestive stimulus activity, due to high concentration of enzymes, than the other Plumbago species, in albino mice and albino rats etc.